Mitochondrial targeting theranostic nanomedicine and molecular biomarkers for efficient cancer diagnosis and therapy - Rout S.K.; Priya V.; Setia A.; Mehata A.K.; Mohan S.; Albratty M.; Najmi A.; Meraya A.M.; Makeen H.A.; Tambuwala M.M.; Muthu M.S. (My University, 2025)
Mitochondria play a crucial part in the cell's ability to adapt to the changing microenvironments and their dysfunction is associated with an extensive array of illnesses, including cancer. Mitochondrial dysfunction has been identified as a potential therapeutic target for cancer therapy. The objective of this article is to give an in-depth analysis of cancer treatment that targets the mitochondrial genome at the molecular level. Recent studies provide insights into nanomedicine techniques and theranostic nanomedicine for mitochondrial targeting. It also provides conceptual information on mitochondrial biomarkers for cancer treatment. Major drawbacks and challenges involved in mitochondrial targeting for advanced cancer therapy have also been discussed. There is a lot of evidence and reason to support using nanomedicine to focus on mitochondrial function. The development of a delivery system with increased selectivity and effectiveness is a prerequisite for a theranostic approach to cancer treatment. If given in large amounts, several new cancer-fighting medicines have been created that are toxic to healthy cells as well. For effective therapy, a new drug must be developed rather than an old one. When it comes to mitochondrial targeting therapy, theranostic techniques offer valuable insight. © 2022 The Authors